Satisfaction and seizure outcomes of epilepsy surgery in tuberous sclerosis: A Swedish population-based long-term follow-up study. (December 2022) - Pearsson, Kevin; Compagno-Strandberg, Maria; Eklund, Erik A.; Rask, Olof; Källén, Kristina
Highlights: Seizure outcomes post epilepsy surgery for tuberculous sclerosis (TSC) are varied. We measured long-term outcomes of epilepsy surgery in TSC in Swedish cohort. We compared hospital/registry reported vs patient reported long term outcomes. Tuberectomy and callosotomy are effective with high overall caregivers' satisfaction. PROMs should be part of future long-term follow-up in epilepsy surgery for TSC. Abstract: Purpose: We conducted a cross-sectional study to evaluate long-term outcomes of epilepsy surgery in tuberous sclerosis complex (TSC) in a Swedish population. Methods: Demographic and seizure data was retrieved from the Swedish National Epilepsy Surgery Registry and medical records. Patient reported outcome measurements (PROM) were determined by telephonic interviews at long term follow-up. Results: Median follow-up was 6 y 8 m (range, 3–15 y 1 m) for tuberectomies ( n  = 15) and 3 y 6 m (range 2–10 y) for callosotomies ( n  = 7). Eight of the 15 tuberectomy participants were seizure-free. Four out of seven callosotomies were free from drop attacks. PROMs were provided by caregivers of 18/20 participants (data missing for two callosotomies). In the tuberectomy group, 6/8 patients were seizure-free and 3/7 had continued seizures; surgery was considered satisfactory and beneficial. Overall, satisfaction was high, even among patients who did not achieve remission; 13/15 tuberectomy responders recommended surgery to others with TSC and refractory epilepsy. None of the patients considered the surgery harmful. In the callosotomy group, satisfaction was low and congruent with the seizure outcome. All patients with continued drop attacks were unsatisfied; one considered surgery to be harmful. One participant, who would not recommend surgery to others, still perceived the surgery to be beneficial. Conclusions: This study confirmed that both tuberectomy and callosotomy are effective treatment options for TSC. Factors other than seizure outcomes seemed to have a major influence on satisfaction and perception of the benefit of surgery.